Challenges and Solutions for Urban Waste Management and Waste Transportation Systems (Case Study: TPS Cikutra, Bandung City) - Zain, Fajrin Meilani Azzahra; Salsabila Putri; Dzalfa Kayla Septia Salma; Salma Nadhif Aghisna; Ammarrafi Rahman Alharits; Arha Ramdhany Bugis; Sultan Dhafa Al-Gibran; Yulia Asyiawati (Journal of Civil Engineering and Planning (JCEP), 2024)
Cikutra TPS (Temporary Waste Disposal Site) often has problems with incoming rubbish, including from rubbish carts or piles of rubbish that eat up roads. This causes traffic jams, disturbs residents' comfort, creates strong odors, and other waste problems. This research aims to identify challenges and provide solutions that can be implemented to improve the performance of waste management and transportation at the Cikutra TPS. The approach method used is qualitative with a normative descriptive analysis method of standards applicable in Indonesia. The research results show that the accumulation of waste due to inadequate TPS capacity, traditional collection and transportation systems, and lack of public awareness is a challenge. The solutions offered are differentiation of transportation patterns, determining fees to improve service quality, government investment in providing ideal transportation facilities and infrastructure, and increasing the ability and will of the community through outreach and training such as a participatory approach that involves the community in waste management, especially organic waste management.